Racial and ethnic disparities in mortality from gastric and esophageal adenocarcinoma. (23rd June 2020) - Laszkowska, Monika; Tramontano, Angela C.; Kim, Judith; Camargo, M. Constanza; Neugut, Alfred I.; Abrams, Julian A.; Hur, Chin
Abstract: Background: Racial/ethnic differences in mortality have not been well studied for either non‐cardia gastric cancer (NCGC) or cardia gastric cancer (CGC). The aim of this study was to examine the US mortality rates for these cancer subtypes, as well as esophageal adenocarcinoma (EAC) as a comparator. Methods: We identified 14 164 individuals who died from NCGC, 5235 from CGC, and 13 982 from EAC in the Surveillance, Epidemiology, and End Results database between 2004 and 2016. Age‐adjusted incidence‐based mortality rates and corresponding annual percent changes (APCs) were calculated. Analyses were stratified by race/ethnicity, age, and stage of disease at diagnosis. Results: The mortality rate in NCGC was two‐ to threefold higher in blacks, Hispanics, and Asians/Pacific Islanders (PI) than non‐Hispanic whites, and was significant across all age groups and stages of disease ( P < .01). Mortality in CGC was higher in non‐Hispanic whites than blacks and Asians/PI, particularly in individuals in the 50‐64 year age group and those with stage IV disease. Mortality in EAC was two‐ to sixfold higher in non‐Hispanic whites than all other groups across all age groups and stages of disease. From 2004 to 2016, mortality rates were stable across all racial/ethnic groups in NCGC and CGC, and in minority groups with EAC, but have been rising in non‐Hispanic whites with EAC (APC 3.03, 95% CI 0.17‐5.96). Conclusions: This is the largest study of incidence‐based mortality in CGC and NCGC and demonstrates racial/ethnic differences in mortality between these subtypes. Mortality rates for NCGC are highest in minority groups, and have been stable in recent years despite declining incidence. Mortality rates for CGC are marginally higher in middle‐aged non‐Hispanic whites with advanced disease, though have remained stable. In contrast, mortality in EAC has been rising for non‐Hispanic whites, in parallel to incidence. Further studies are needed to refine prevention strategies for high‐risk individuals dying from these specific cancer subtypes. Abstract : This study examined the US incidence‐based mortality rates for cardia and non‐cardia gastric cancer, as well as esophageal adenocarcinoma as a comparator, and found distinct trends. Mortality was higher in blacks, Hispanics, and Asians/Pacific Islanders compared to non‐Hispanic whites in non‐cardia gastric cancer, but higher in non‐Hispanic whites in cardia gastric cancer and esophageal adenocarcinoma. Further studies are needed to refine prevention strategies for high‐risk individuals dying from these specific cancer subtypes.